2014
DOI: 10.1159/000363137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an Isoenergetic Traditional Mediterranean Diet on the High-Density Lipoprotein Proteome in Men with the Metabolic Syndrome

Abstract: Background/Aims: The objective of this preliminary study was to examine the impact of the Mediterranean diet (MedDiet) on the high-density lipoprotein (HDL) proteome in men with the metabolic syndrome (MetS). Methods: Twenty-six men with the MetS first consumed a standardized baseline North American isoenergetic control diet (5 weeks) and then consumed an isoenergetic MedDiet (5 weeks), both in full feeding condition. The HDL fraction was isolated by ultracentrifugation at the end of each diet and the HDL prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…81 The other study was a fixed-sequence study that presented Lp-PLA 2 as percentage change only, which limited the usefulness of the data. 91 In that study, the small number of people whose HDL cholesterol was noted to have increased (n ¼ 6 compared with n ¼ 6 with reduced HDL), and there was a trend toward a favorable impact on Lp-PLA 2 ; however, the results were not significant. 91 Four studies examined vegetarian dietary patterns.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…81 The other study was a fixed-sequence study that presented Lp-PLA 2 as percentage change only, which limited the usefulness of the data. 91 In that study, the small number of people whose HDL cholesterol was noted to have increased (n ¼ 6 compared with n ¼ 6 with reduced HDL), and there was a trend toward a favorable impact on Lp-PLA 2 ; however, the results were not significant. 91 Four studies examined vegetarian dietary patterns.…”
Section: Resultsmentioning
confidence: 80%
“…91 In that study, the small number of people whose HDL cholesterol was noted to have increased (n ¼ 6 compared with n ¼ 6 with reduced HDL), and there was a trend toward a favorable impact on Lp-PLA 2 ; however, the results were not significant. 91 Four studies examined vegetarian dietary patterns. One study was an RCT and compared similar Indian vegetarian diets that differed in the addition of either coconut or peanuts.…”
Section: Resultsmentioning
confidence: 80%
“…Even though the lower level of HDL cholesterol is a risk factor for the development of CVD, an association between low-fat diet and increased CVD risk has not been established. In efforts to clarify this phenomenon, some studies demonstrated that despite the overall reduction in HDL in response to low-fat diet, HDL/apolipoprotein subtypes that are responsible for cholesterol metabolism were functionally preserved [68,69]. Another lipid profile component that has an established long-standing association with CVD is the plasma level of triglycerides.…”
Section: Discussionmentioning
confidence: 99%
“…HDLs could act as transporters of several derivatives of olive oil phenolic compounds to the endothelial cells where they may prevent oxidative damage in cell mitochondria and preserve the production of nitric oxide, as described in vitro [35,37]. [38] has been reported to decrease the content of acute-phase proteins in HDLs and may, therefore, promote a less pro-inflammatory state of the particles.…”
Section: Hdl Anti-inflammatory and Vasoprotective Effectsmentioning
confidence: 98%